Protection from Group B Streptococcal Infection in Neonatal Mice by Maternal Immunization with Recombinant Sip Protein - Martin, Denis (American Society for Microbiology, 2002)
The protective potential of antibodies directed against group B streptococcus (GBS) Sip surface protein was determined by using the mouse neonatal infection model. Rabbit Sip-specific antibodies administered passively to pregnant mice protected their pups against a GBS lethal challenge. In addition, active immunization with purified recombinant Sip protein of female CD-1 mice induced the production of specific antibodies that also confer protection to the newborn pups against GBS strains of serotypes Ia/c, Ib, II, III, and V. These data confirm that Sip-specific antibodies can cross the placenta and conferred protective immunity against GBS infections.